ASSESSMENT OF TOXIC MATERIALS IN SUNAF MARSH - selman, Mohammed (University of Thi-Qar Journal of Science, 2011)
This paper presents studying the pollution of water in Al-Sunaf marsh (Alkhawisa village)by evaluating its water quality which has physical and chemical properties and comparing themwith the world health organization standards (WHO1993). Results show that the pollutants(TSS, Salinity, Cl- , K+ , Na+ , Co, Cu, Zn, PO4 -2 ) are not exceeding its guide levels. Also resultsshow chronic effects of some chemical and physical properties, These Chronic effects resultfrom the increasing of monthly concentrations for (Turbidity, Calcium, Chromium, Lead,Magnesium, Cadmium, Barium, Iron, Sulfate, chloride, Nickel and TDS) from its guide levelwhich produce health and hazard effects on peoples who live in the boundaries of Sunaf marsh(Alkhawisa village), Results prevent the ability to use this water for different purposes.